DESIGN EVALUATION OF AN ELECTRIC TRIKE BASED ON THE EFFICIENCY OF VARIOUS COMPONENT CONFIGURATION - Riananta Arya, Rafi
The development of E-Trike as an extended-range electric vehicle gives the need for the prediction of the E-Trike’s performance as an extended-range electric vehicle and as an ordinary battery electric vehicle. The performance prediction model is based on previous studies, which processes the speed and positional altitude of a vehicle each second into the battery state-of-charge (SOC) and its energy consumption each second. The simulation is used to find the best possible component configuration for the E-trike, for its usage in Bandung. Various simulations are done using two battery types, three braking strategies, the presence of range extender, and various mass of range extender. The input data for the model is the speed and altitude that is obtained using a GPS application, while a motorcycle is traveling through certain routes in Bandung. The route is chosen based on the time and distance target needed. The results of the simulation showed that the base case of the E-Trike is not effective, and only several cases managed to finish the route with less than 10% remaining SOC. The most efficient and effective configuration is to use the serial regenerative braking strategy with no range extender equipped. This configuration achieves an efficiency of 18.07 km/kWh for the first route. For the complete route, the usage of 20kg range extender is needed to prevent the SOC to drop below 30%. The NCA with serial regenerative braking and 20kg range extender has an efficiency of 17.47 km/kWh for the complete route.